Polymorphisms in Lysyl Oxidase Family Genes Are Associated With Intracranial Aneurysm Susceptibility in a Chinese Population - Luo, Chun; Hu, Chongyu; Li, Bingyang; Liu, Junyu; Hu, Liming; Dong, Rui; Liao, Xin; Zhou, Jilin; Xu, Lu; Liu, Songlin; Li, Yifeng; Yuan, Dun; et al. (Frontiers in Endocrinology, 2021)
Background: Intracranial aneurysms (IA) comprise a multifactorial disease with unclear physiological mechanisms. The lysyl oxidase (LOX) family of genes (LOX, LOX–like 1–4) plays important roles in extracellular matrix (ECM) reconstruction and has been investigated in terms of susceptibility to IA in a few populations. We aimed to determine whether polymorphisms in LOX family genes are associated with susceptibility to IA in a Chinese population. Methods: This case-control study included 384 patients with IA and 384 healthy individuals without IA (controls). We genotyped 27 single nucleotide polymorphisms (SNPs) of LOX family genes using the Sequenom MassARRAY® platform. These SNPs were adjusted for known risk factors and then, odds ratios (OR) and 95% confidence intervals (CI) were evaluated using binary logistic regression analysis. Results: The result showed that LOX rs10519694 was associated with the risk of IA in recessive (OR, 3.49; 95% CI, 1.02–12.00) and additive (OR, 1.51; 95%CI, 1.01–2.26) models. Stratified analyses illustrated that LOX rs10519694 was associated with the risk of single IA in the recessive (OR, 3.95; 95%CI, 1.04–15.11) and additive (OR, 1.64; 95%CI, 1.04–2.56) models. The LOXL2 rs1010156 polymorphism was associated with multiple IA in the dominant model (OR, 1.92; 95%CI, 1.02–3.62). No associations were observed between SNPs of LOXL1, LOXL3, and LOXL4 and risk of IA. Conclusion: LOX and LOXL2 polymorphisms were associated with risk of single IA and multiple IA in a Chinese population, suggesting potential roles of these genes in IA. The effects of these genes on IA require further investigation.